2011
DOI: 10.1007/s12070-011-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Dacryocystorhinostomy with Flap Suturing

Abstract: Multiple reports have demonstrated the efficacy of endoscopic dacryocystorhinostomy (DCR). However the results of the same have varied from centre to centre. Many still regard external DCR as the gold standard. To describe an endoscopic DCR technique which anatomically simulates an external DCR and assess its results. Prospective, nonrandomized and noncomparative interventional case series. Clinical charts of patients with nasolacrimal duct obstruction based on symptomatic, clinical and radiological basis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…However, a statistically lower number of postoperative debridement sessions was noted [18]. Kirtane et al [19] described using 5-0 vicryl suture or vascular clips to bring the mucosal and medial lacrimal sac flaps together. The authors reported primary success in 19 of 20 EN-DCRs with nasolacrimal duct obstruction.…”
Section: Mucosal Flapsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a statistically lower number of postoperative debridement sessions was noted [18]. Kirtane et al [19] described using 5-0 vicryl suture or vascular clips to bring the mucosal and medial lacrimal sac flaps together. The authors reported primary success in 19 of 20 EN-DCRs with nasolacrimal duct obstruction.…”
Section: Mucosal Flapsmentioning
confidence: 99%
“…Kirtane et al [19] described using 5-0 vicryl suture or vascular clips to bring the mucosal and medial lacrimal sac flaps together. Kirtane [19] also noted that his outcomes with vascular clips were similar to those for sutures, with the advantage of being easier to use. The 20th case was ultimately successful after removal of a granuloma at the surgical fistula.…”
Section: Mucosal Flapsmentioning
confidence: 99%
“…sutured mucosal and medial lacrimal sac flaps together, with size 5-0 vicryl sutures, to prevent restenosis. They reported primary success in 19 of 20 patients with nasolacrimal duct obstructions 18 …”
Section: Discussionmentioning
confidence: 99%
“…Kirtane и соавт. [54] предложили использовать технику эндоназальной эндоскопической ДЦР, включающую создание лоскута слизистой оболочки полости носа с основанием кзади, выкраивание аналогичного лоскута из медиальной стенки слезного мешка и затем их фиксацию двумя швами.…”
Section: формирование лоскутов слизистой оболочки полости носаunclassified